2022
DOI: 10.3389/fimmu.2022.1040600
|View full text |Cite
|
Sign up to set email alerts
|

Unique CLR expression patterns on circulating and tumor-infiltrating DC subsets correlated with clinical outcome in melanoma patients

Abstract: Subversion of immunity by tumors is a crucial step for their development. Dendritic cells (DCs) are strategic immune cells that orchestrate anti-tumor immune responses but display altered functions in cancer. The bases for such DCs’ hijacking are not fully understood. Tumor cells harbor unusual glycosylation patterns of surface glycoproteins and glycolipids. DCs express glycan-binding receptors, named C-type lectin receptors (CLR), allowing them to sense changes in glycan signature of their environment, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 88 publications
1
16
0
Order By: Relevance
“…Further investigating the underlying mechanism of the glycanmediated effect on DCs would be very relevant. In our previous work (32), we documented a link between glycan motifs on tumor cells and perturbed CLR profiles on tumor-infiltrating DC subsets. The glycoprofile of primary melanoma tumor cell lines revealed high level of Man, Fuc and GlcNAc motifs.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Further investigating the underlying mechanism of the glycanmediated effect on DCs would be very relevant. In our previous work (32), we documented a link between glycan motifs on tumor cells and perturbed CLR profiles on tumor-infiltrating DC subsets. The glycoprofile of primary melanoma tumor cell lines revealed high level of Man, Fuc and GlcNAc motifs.…”
Section: Discussionmentioning
confidence: 88%
“…These motifs are known to be recognized by Dectin 1 (specific for β-glucans), DCIR, DC-SIGN and CD206 (specific for Man, Fuc and GlcNAc motifs). Strikingly, these CLRs are the one that were the most modulated on tumor-infiltrating DC subsets from melanoma patients ( 32 ). We highlighted strong link between specific glycans and corresponding CLR on DCs within the tumor of melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggest in a few cancer types an immunosuppressive role of altered tumor glycosylation on innate immune responses through modulation of immune cells’ function [ 100 ]. In melanoma patients, we recently highlighted that the CLR profiles in circulating and tumor-infiltrating DC subsets display strong perturbations, correlated with unique DCs’ features, and dictated clinical outcomes [ 101 ]. Furthermore, the melanoma tumor glycocode directly affects the DC subsets’ functionality [ 102 ], revealing the glycan/CLR axis as a potential DC subversion pathway in melanoma.…”
Section: DC Subsets In Melanoma: Heterogeneity Function Subversion An...mentioning
confidence: 99%
“…These two DC subsets trigger pro-tumour regulatory responses, exhibit altered crosstalk with anti-tumour immune effector cells [19,20], and have been associated with poor clinical outcome. We previously revealed that circulating and tumour-infiltrating DCs from melanoma patients display major perturbations in their CLR expression profiles [21]. Furthermore, melanoma hijacks DCs by secreting immunosuppressive factors (e.g., gangliosides, interleukin [IL]-6, IL-10, transforming growth factor-β, prostaglandin-E2) and immunomodulatory molecules (e.g., thymus-and activation-regulated chemokine [TARC]/CC chemokine ligand [CCL]17, macrophagederived chemokine [MDC]/CCL22) [19], by inducing metabolic stress which interferes with DC differentiation, recruitment, maturation and function, or also by promoting regulatory responses and Th2 polarisation [22,23].…”
Section: Introductionmentioning
confidence: 99%